2022
DOI: 10.1111/jfb.14941
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance movements of Antarctic toothfish (Dissostichus mawsoni) as inferred from tag‐recapture data

Abstract: Examining the causes and consequences of animal movement is fundamental to understanding the ecology of any species. This analysis focuses on Antarctic toothfish movements in the Southern Ocean as inferred from tagging data collected from 2001 to 2019 with a focus on the characteristics of long-distance movements, defined as an individual recaptured greater than 200 km from their release location.The results of this analysis indicate that while adult Antarctic toothfish are generally quite sedentary a small pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Patagonian toothfish support fisheries around the sub-Antarctic regions and understanding spatial stock structure is an important component in precautionary and sustainable management. Multiple studies have been carried out to identify stock structure of both toothfish species, including analysis of tagged fish movements [ 4 , 47 ], mineral deposits within otoliths [ 48 ], microsatellites [ 49 ], and SNP/RAD-Seq phylogenetic markers [ 50 ]. The Patagonian toothfish genome sequences provided by this study will further strengthen the resources available for population genetics, allowing identification of the most suitable restriction enzymes to use for RAD-Seq analysis [ 51 , 52 ], guiding the choice of neutral markers or restriction enzymes based on proximity to gene coding regions [ 53 ] and allowing a scan of the genome to identify regions showing higher levels of adaptive or balancing selection [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patagonian toothfish support fisheries around the sub-Antarctic regions and understanding spatial stock structure is an important component in precautionary and sustainable management. Multiple studies have been carried out to identify stock structure of both toothfish species, including analysis of tagged fish movements [ 4 , 47 ], mineral deposits within otoliths [ 48 ], microsatellites [ 49 ], and SNP/RAD-Seq phylogenetic markers [ 50 ]. The Patagonian toothfish genome sequences provided by this study will further strengthen the resources available for population genetics, allowing identification of the most suitable restriction enzymes to use for RAD-Seq analysis [ 51 , 52 ], guiding the choice of neutral markers or restriction enzymes based on proximity to gene coding regions [ 53 ] and allowing a scan of the genome to identify regions showing higher levels of adaptive or balancing selection [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…al. 2022, Grilly et al, 2021), mineral deposits within otoliths (Ashford et al ., 2008), microsatellites (Smith and McVeagh, 2000) and SNP/RAD-Seq phylogenetic markers (Arkhipkin et al ., 2022; Maschette et al ., 2019). The Patagonian toothfish genome sequences provided by this study will further strengthen the resources available for this area of applied research, allowing identification of the most suitable restriction enzymes to use for RAD-Seq analysis (Arnold et al ., 2013; Lepais and Weir, 2014), guiding the choice of neutral markers or restriction enzymes based on proximity to gene coding regions (Luikart et al ., 2003) and allowing a scan of the genome to identify regions showing higher levels of adaptive or balancing selection (Beaumont and Balding, 2004; Cornman et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tagging, be it conventional or electronic, has shown most Patagonian toothfish tend to remain within a 50-km radius from their release sites (Brown et al, 2013;Farrugia, 2018;Lee et al, 2022;Troccoli et al, 2023). Recapture distances of > 200 km are observed in less than 10% of tagged fish, even though adults can undertake journeys in excess of 5000 km (CCAMLR Secretariat, 2017;Grilly et al, 2022). Earlier studies have therefore concluded that Patagonian toothfish exhibit year-round site fidelity (Collins et al, 2010;Lee et al, 2022) and extended periods of limited displacement (up to 8 years, Troccoli et al, 2023), implicating specific life history choices adopted by Patagonian toothfish, such as the maximization of energy savings through reduced migratory dispersals (Collins et al, 2010;Lee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%